2022
DOI: 10.3233/jpd-212749
|View full text |Cite
|
Sign up to set email alerts
|

Management of Sleep Disturbances in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is defined by its motor symptoms rigidity, tremor, and akinesia. However, non-motor symptoms, particularly autonomic disorders and sleep disturbances, occur frequently in PD causing equivalent or even greater discomfort than motor symptoms effectively decreasing quality of life in patients and caregivers. Most common sleep disturbances in PD are insomnia, sleep disordered breathing, excessive daytime sleepiness, REM sleep behavior disorder, and sleep-related movement disorders such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 296 publications
1
14
0
Order By: Relevance
“…Sleep problems are common nonmotor PD symptoms and can be observed in both the prodromal and early stages ( 190 ). The most common sleep disorders are insomnia, sleep disordered breathing, excessive daytime sleepiness, RBD, and sleep-related movement disorders, such as restless legs syndrome ( 191 ). We know that RBD is a strong predictor of subsequent PD ( 60 , 62 ), therefore early detection of sleep problems in older people, in particular RBD, may provide an opportunity for early intervention to treat the sleep disorder itself and to prevent the development of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep problems are common nonmotor PD symptoms and can be observed in both the prodromal and early stages ( 190 ). The most common sleep disorders are insomnia, sleep disordered breathing, excessive daytime sleepiness, RBD, and sleep-related movement disorders, such as restless legs syndrome ( 191 ). We know that RBD is a strong predictor of subsequent PD ( 60 , 62 ), therefore early detection of sleep problems in older people, in particular RBD, may provide an opportunity for early intervention to treat the sleep disorder itself and to prevent the development of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Exercising during the day, including regular physical activity in the morning and scheduled rehabilitation, may improve many non-motor symptoms in PD, including a reduction of fatigue, an increase in sleep quality, and a reduction of EDS. In addition, outdoor activities and avoiding vigorous physical activity 3-4 h before sleeping might also be helpful in this process (van der Kolk and King, 2013;Schütz et al, 2022). When a circadian rhythm dysfunction is detected (e.g., delayed sleep-wake phase disorder), supplementary exposure to bright light using light therapy in the morning might have beneficial effects on EDS by influencing circadian rhythm; however, there is no consensus on a therapeutic protocol in PD patients, and the efficacy must be proved by more studies (Lin , 2021).…”
Section: Non-pharmacological Interventionmentioning
confidence: 99%
“…RBD is a sleep disorder characterised by a failure of muscle atonia during REM resulting in dream enactment and other sleep behaviours (Schütz et al, 2022). RBD is a common early sleep complaint in neurodegenerative α‐synucleinopathy diseases (Boeve et al, 2001) and is reported in up to 60% of PD patients; its prevalence is associated with age, male sex, disease severity, duration of motor symptoms and dopaminergic therapy (Lee et al, 2010; Zhu et al, 2017).…”
Section: Sleep Disorders and Disturbances In Parkinson's Diseasementioning
confidence: 99%